2006
DOI: 10.1016/j.beth.2005.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Rebound Effects Following Deliberate Thought Suppression: Does PTSD Make a Difference?

Abstract: This study was designed to examine the effects of deliberate suppression of trauma-related thoughts in 44 individuals who were PTSD+ and 26 individuals who were PTSD− following a motor vehicle accident (MVA). In an effort to resolve discrepancies in the literature, the PTSD− group was selected from the same help-seeking population as the patient group. Measures included the percentage of MVA-related thoughts, mood, perceived controllability of thoughts, and physiological arousal (heart rate, skin conductance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 42 publications
2
21
1
Order By: Relevance
“…In this task, the PTSD group did not experience a rebound effect, suggesting that this effect was specific to the suppression of their trauma-related thoughts. However, in a further follow up study (Beck, 2006), both PTSD and no-PTSD groups showed a post-suppression rebound of trauma-related thoughts, suggesting that difficulties in suppressing trauma-related thoughts may be ubiquitous after exposure to trauma, and not specific to PTSD.…”
Section: Anxiety Disordersmentioning
confidence: 81%
See 1 more Smart Citation
“…In this task, the PTSD group did not experience a rebound effect, suggesting that this effect was specific to the suppression of their trauma-related thoughts. However, in a further follow up study (Beck, 2006), both PTSD and no-PTSD groups showed a post-suppression rebound of trauma-related thoughts, suggesting that difficulties in suppressing trauma-related thoughts may be ubiquitous after exposure to trauma, and not specific to PTSD.…”
Section: Anxiety Disordersmentioning
confidence: 81%
“…In this task, the PTSD group did not experience a rebound effect, suggesting that this effect was specific to the suppression of their trauma-related thoughts. However, in a further follow up study (Beck, 2006), both PTSD and no-PTSD groups showed a post-suppression rebound of trauma-related thoughts, suggesting that difficulties in suppressing trauma-related thoughts may be ubiquitous after exposure to trauma, and not specific to PTSD.Finally, correlational studies have shown an association between the tendency for chronic suppression and the severity of PTSD symptoms (e.g., Vazquez et al, in press). Taken together, results to date suggest that the mental effort expended in the suppression of trauma-related thoughts serves only to exacerbate trauma-related intrusions and consequent distress.…”
mentioning
confidence: 96%
“…[3] Evidence for rebound effects has been mixed, with multiple studies failing to find an effect (e.g., [4,5] ). Others report rebound effects, particularly in dysphoric or clinical samples (e.g., [6][7][8][9][10] ). Evidence that thought suppression promotes symptoms of emotional distress is also mixed: a majority of studies supports an association [1,[3][4][5]7,11] , but others fail to find a relation (e.g., [12] ).…”
Section: Introductionmentioning
confidence: 96%
“…Others report rebound effects, particularly in dysphoric or clinical samples (e.g., [6][7][8][9][10] ). Evidence that thought suppression promotes symptoms of emotional distress is also mixed: a majority of studies supports an association [1,[3][4][5]7,11] , but others fail to find a relation (e.g., [12] ). It has been hypothesized that thought suppression is driven by thought-action fusion, the belief that having a thought about an action or event is morally akin to carrying out that action or increases the likelihood of the event occurring.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, cumulative findings suggest that even individuals who should be extremely motivated to forget their traumas are largely unable to do so. In addition, experiments instructing participants to discount, disregard, or generally push unwanted thoughts out of awareness often result in a boomerang effect, thereby increasing the prominence and accessibility of these thoughts (e.g., Beck, Gudmundsdottir, Palyo, Miller, & Grant, 2006;Shipherd & Beck, 1999;Wegner, 1994). …”
Section: A Few Problems With Freudian Repression Of Memoriesmentioning
confidence: 99%